2022
DOI: 10.1039/d2ra07238f
|View full text |Cite|
|
Sign up to set email alerts
|

Molybdenum-doped iron oxide nanostructures synthesized via a chemical co-precipitation route for efficient dye degradation and antimicrobial performance: in silico molecular docking studies

Abstract: In this research, various concentrations of molybdenum (2, 4 and 6 wt%) doped Fe3O4 nanostructures (Mo-Fe3O4 NSs) were prepared via a co-precipitation technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 68 publications
0
21
0
Order By: Relevance
“…The potential involvement of nanostructures as bactericidal agents has widely been documented; yet, the reason for their efficacy remains a mystery. The disruption of many cellular processes by antagonizing enzyme targets is regarded as a viable technique for discovering novel antibacterial drugs. , In the case of FabI E. coli , both CS-doped La 2 O 3 and CS- and CDs-doped La 2 O 3 exhibited excellent binding scores of 4.76 and 5.50, respectively. Nine H-bonds, namely, Gly13, Ser19, Ile20, Ser91, Ile92, Gly93, Tyr156, Pro191, and Ile192, were the primary contributors to the formation of the docked complex in CS-doped La 2 O 3 nanocomposites (Figure a,b).…”
Section: Resultsmentioning
confidence: 99%
“…The potential involvement of nanostructures as bactericidal agents has widely been documented; yet, the reason for their efficacy remains a mystery. The disruption of many cellular processes by antagonizing enzyme targets is regarded as a viable technique for discovering novel antibacterial drugs. , In the case of FabI E. coli , both CS-doped La 2 O 3 and CS- and CDs-doped La 2 O 3 exhibited excellent binding scores of 4.76 and 5.50, respectively. Nine H-bonds, namely, Gly13, Ser19, Ile20, Ser91, Ile92, Gly93, Tyr156, Pro191, and Ile192, were the primary contributors to the formation of the docked complex in CS-doped La 2 O 3 nanocomposites (Figure a,b).…”
Section: Resultsmentioning
confidence: 99%
“…The prominent oxygen peak in doped samples generated from PAA, chemical formula (C 3 H 4 O 2 ) n . 64 The chloride (Cl) and sodium (Na) peaks ascribed to HCl and NaOH were used in the synthesis to sustain the pH. The Ag peak confirmed the existence of Ag in doped samples, while small Au peaks attributed to the coating on the samples minimized charging effects 52,65 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[24][25][26]28,30,32 Studies of NDI and ZDI have shown higher MIC with the lowest amount on E. coli, B. subtilis, S. typhi, K. pneumonia, while MDI has shown no significant inhibition of E. coli at the highest concentration (Table 1). 32 MIC and minimum bactericidal concentration were not reported in most studies. 25,[29][30][31][32]34,36,51,116 Although research by Ivashchenko et al ( 2015) reported a higher antimicrobial activity of doped-IONPs combined with antibiotics.…”
Section: Doped-iron Oxide Nanoparticles (Doped-ionps)mentioning
confidence: 99%
“…118 Doped-IONPs and bare IONPs shared similar mechanism of actions from generating ROS for disrupting the bacterial DNA and membrane, leading to cell death eventually. 25,[28][29][30][31][32]34,36,51,52,116…”
Section: Doped-iron Oxide Nanoparticles (Doped-ionps)mentioning
confidence: 99%